Proof Complexity of Hard-Determinable Balanced Tautologies in Frege Systems - Chubaryan, Anahit A. (Mathematical Problems of Computer Science, 2022)
Hard-determinable property and balanced property of tautologies are specified as important properties in the study of proof complexities formerly. In this paper hard-determinable and balanced properties are studied together. It is shown that some sequences of hard determinable balanced tautologies have polynomially bounded Frege proofs.